Examining Some Serious Challenges and Possibility of AI Emulating Human Emotions, Consciousness, Understanding and ‘Self’ - Tariq, Sadia; Iftikhar, Asif; Chaudhary, Puruesh; Khurshid, Khurram (Journal of NeuroPhilosophy, 2022)
This research falls in the ambit of ‘AI and Philosophy’. It explores why emulating the complex processes of subjective experience, emotions, consciousness, self-awareness, and the human personality, will be a huge challenge for AI research. It touches upon some finer aspects, like the huge variety of human emotions and feelings, processes of future and fringe consciousness, and the evolution of self-awareness and complex human self/personality, whose practical realization in an AI system would be very difficult, if not impossible. In the backdrop of these serious challenges it also discusses an interesting possibility of emulation in the field of Hermeneutics, focusing on hermeneutics of ṣan‘at-e ihām (construction of ambiguity) in Urdu, Persian, Arabic, Hindi, and Punjabi poetry. The basic purpose of this work is to underscore the critical importance of this area for AI research, and to shed light on those aspects of consciousness, emotions, awareness, understanding and self whose comprehension and inclusion is necessary in designing and constructing AI systems that can parallel human mental functioning.